When Organizational Performance Matters for Personnel Decisions: Executives' Career Patterns in a Conglomerate. (December 2020) - Kim, Jonghwan
Abstract: This study examines whether the performance of a business unit affects the likelihood of employees' promotion in an organization and explores potential moderators of the relationship. Using a sample of 4, 657 executive-years in Samsung Group affiliates, it finds that promotions are more likely with good organizational performance, as measured in terms of employment growth and return on assets (ROA). The main finding is robust to alternatively specified ROA variables. The results reveal that the association (i) exists only for rank promotions with a substantial increase in compensation but not for function promotions involving substantial job changes, (ii) is significant only for executives at relatively lower ranks, and (iii) is stronger in business units that allow more frequent internal transfers. The findings from the conglomerate suggest practical enabling mechanisms by which large, decentralized, and growth-decelerating firms can overcome a tradeoff between the maximization of promotion-based incentives and the efficient operation of a hierarchy.